Teaching Music in English: A Content- Based Instruction Model in Secondary Education - Lucía Bellés-Calvera (Universidad de La Sabana, 2018)
Over the past few years, there has been a growing interest in the teaching and learning of several languages in an attempt to generate multilingual education opportunities, particularly in Europe. In response to the demands of our globalized society, Content-Based Instruction (CBI), which has also been referred to as "immersion and Content and Language Integrated Learning (CLIL) programs," emerged as a teaching approach that combines the learning of curricular contents and the communicative competence in the target language. This study was carried out at a public high school set in a Spanish bilingual community, where music is taught through a CLIL approach in English class. The purpose of this paper is to examine how students value their music lessons in English and to check the adequacy of teaching music as a subject in English. To achieve this goal, materials adapted to their level of proficiency and a final questionnaire were designed. Results indicate that students are satisfied with this proposal, since they consider these music lessons to be easier than the regular ones. Not only did they enjoy being exposed to English in these music lessons, but a considerable number of students would also like to take a CLIL program in the near future. Pedagogical implications to this CBI model account for the development of learners' autonomy, the use of audio-visual aids and further research in bilingual and multilingual regions overseas.